A survey on blockchain for intelligent governmental applications - Ibrahim Ramadan Abdelhamid; Islam Tharwat Abdel Halim; Abd El-Majeed Amin Ali; Ibrahim Abdelmoniem Ibrahim (Institute of Advanced Engineering and Science, 2023)
Blockchain technology has attracted a lot of attention lately because it is seen as an all-purpose method for conducting online transactions between unidentified parties without the need for a centralized authority. Modern developers and businesspeople think it will disrupt or even change both the government and industry. In this setting, government-focused blockchains are becoming increasingly prevalent. Several recent studies highlighted use cases in the public sector for decentralized information infrastructures. Blockchain is expected to revolutionize or at least simplify many governmental functions. However, because blockchain use has yet to be widely adopted in government or industrial settings, the question arises: what are the technical hurdles impeding blockchain adoption? To that purpose, a systematic literature assessment of 29 academic articles investigating software engineering problems in blockchain technology for government applications has been done. The papers are initially inductively analyzed in order to illustrate and identify the issues frequently highlighted in academic literature. Furthermore, a theoretical framework is discussed by relying on models used in traditional software development, which is then followed by deductive analysis to map out the blockchain use cases and future trends connected to the difficulties.